Treatment and prevention of trichuriasis : efficacy of albendazole in disadvantaged children at Rawsonville Primary School, Western Cape Province, South Africa - Arendse, Vera Jane (Stellenbosch : Stellenbosch University, 2012)
Thesis (MSc)--Stellenbosch University, 2000.